Analisis Rasio Keuangan untuk Memprediksi Kondisi Financial Distress (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2015) - Verani Carolina; Elyzabet Indrawati Marpaung; Derry Pratama (Jurnal Akuntansi, 2017)
AbstractThis research aims to examine wether liquidity, profitability, leverage, and operating cash flow can be used as financial distress predictor. Manufacturing companies which were listed in the Indonesia Stock Exchange during the period 2014-2015, were used as samples. This research used purposive sampling method and 96 companies can be used as samples according to the criteria. Data was analyzed using logistic regression. The result showed that only profitability can be used as financial distress predictor, while liquidity, leverage, and operating cash flow cannot.Keywords: Financial Distress, Liquidity, Leverage, Operating Cash Flow, and Profitability